PENGARUH KEPRIBADIAN TIPE D TERHADAP KEPUASAAN HIDUP YANG DIMEDIASI OLEH DUKUNGAN SOSIAL PADA MAHASISWA S1 FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS SYIAH KUALA - Helvy Ramadhani; Amri Amri (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2020)
This study aims to measure the effect of Type D Personality to undergraduate student’s Life Satisfaction in Economic and Business Faculty of Syiah Kuala University with Social Support as mediating variable. The sample used in this study were active undergraduate student’s in odd semester 2018/2019 is totalling 240 respondents. Data collection equipment used in this study was a questionnaire. The sampling technique used is Proportionated Stratified Random Sampling. Hierarchical Linear Modelling (HLM) was used as a method of analysis to determine the effect of all the variables involved. Based on the result of the HLM analysis indicated that Type D Personality negatively influence Life Satisfaction, Type D Personality negatively influence Social Support, Social Support positively influence Life Satisfaction and Social Support mediate the relationship between Type D Personality and Life Satisfaction.